The effect of planting technique on the growth of two Shorea species in Gunung Dahu, Bogor, Indonesia - Henti H Rachmat; PRIJANTO PAMOENGKAS; LUSIANA SHOLIHAH; RIZKI ARY FAMBAYUN; Arida Susilowati (Society for Indonesian Biodiversity, 2020)
One of the rehabilitation efforts undertaken by the Forest Research and Development Center in Bogor was to establish a mixed meranti(Dipterocarp) forest in the Gunung Dahu Research Forest, Bogor - West Java. The rehabilitation activities adopted several planting techniques, including total and line planting, used several types of red meranti (Shorea spp.). The purpose of this study was to assess the success of rehabilitation effort by analyzing the growth performance of Shorea leprosula and Shorea selanicastands in which applying total and line planting techniques. Diameter and height, as well as environmental factors such as soil texture, average litter thickness, slope, the average thickness of topsoil, and canopy density, were plant growth parameters that were observed. Growth data analysis was performed using ANOVA and followed by Duncan's test. The results showed that planting techniques affected the diameter growth. The highest growth rate was found in S. selanicaspecies with line planting techniques with the average diameter and height increment was 1.13 cm/year and 0.78 cm/year. Line planting techniques also scored the highest value of basal area and stand volumes, 0.06 m2 and 0.64 m3per year for S. leprosulaand 0.06 m2and 0.66 m3per year for S. selanica.